Evaluating Ecohydrological Separation with Geochemical Tracers, Δ2H and Δ18O, from Northern California in an Irrigated and Semi-arid Setting - (:unkn) unknown (My University, 2018)
The two water worlds hypothesis challenges the widely accepted ecohydrology tenet that plant roots access a single, homogeneous reservoir of soil water (McDonnell, 2014). This project aspired to advance the understanding of the two water worlds, or ecohydrological separation (ES) of soil water reservoirs, applied to an irrigated agricultural setting. This study also aimed to correlate plant root morphology with plant water uptake. Using geochemical tracers, δ2H and δ18O, isotopic analysis of soil and plant tissue was used to evaluate irrigated plant water acquisition. Field work was conducted on two irrigated farms, Full Belly Farm and Riverdog Farm, in the Capay Valley of northern California, where the Mediterranean climate best exhibits ES. The fact that northern California is both an agricultural hub and drought-prone region makes this location a particularly interesting area to conduct precision agriculture research. Overall, results for the original objectives of this project were inconclusive due to a lack of method development. Taking on a new direction, the redirected focus of this project aimed to use soil water isotopes to determine the pre-evaporative isotopic composition of soil water. The intersection between the local meteoric water line (LMWL) and linear regression through soil water isotopes for a given location was inferred to be the pre-evaporative soil water isotopic signature. This research serves as a platform for future agriculture-based ES experimental designs using water isotopes. Future work can improve upon sample collection, sample processing, and isotopic analysis methods discussed in this project. With improved methodologies, future iterations of this project can work towards refining precision irrigation practices based on new understandings of soil water storage and transport in the soil-plant-atmosphere system.
Keywords: distillation; ecohydrology; hydrology; isotope; plant